Problem uchodźców i migracji w optyce Deklaracji Haskiej z 2002 r. - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The problem of fugitives, migrants and internally displaced persons constitutes one of the more important issues in internal politics of individual states as well as in international relations. An attempt to establish the principles and set directions for such a policy is expressed in the Hague Declaration, adopted in 2002 as motioned for by the Dutch  local  chapter  of  the  Society  for  International  Development  (SID). The paper presents and reviews the contents of the Declaration, which emphasizes the responsibility of states for the situation of refugees and migrants and the need to establish the principles of such a policy. It also refers to the problems of regulated and non-regulated migration, the issue of assimilation, integration, the law of migrants to return and the duties of state institutions, local governments, religious organizations and social institutions in the reception countries. The Declaration addresses political and economic reasons for migration and it emphasizes that the work of fugitives and migrants does not only bring benefits to them, but also to the reception countries and families in the homeland. The Declaration pays particular attention to children and female refugees and to the need for specific regulations in this respect. It refers to human rights while observing the inertia and lack of concepts of specialized international agencies.